Achieving refined microstructures and improved mechanical properties in a cup-shaped Mg-Gd-Y-Zr alloy casting by novel near-liquidus squeeze cast process - Cunlong Wang; Qiuxu Chen; Jianghao Chen; He Xie; Wencai Liu; Liang Zhang; Guohua Wu (Journal of Materials Research and Technology)
We have recently proposed a novel process named low frequency electro-magnetic stirring assisted near-liquidus squeeze cast (NSC), which has been shown effective grain refinement effect in pure Mg and binary Mg-RE alloys. In this work, the NSC process was introduced for fabricating of a cup-shaped casting by Mg-Gd-Y-Zr alloy (VW103K). The cup-shaped VW103K alloy castings fabricated by NSC process show good surface quality and dimensional accuracy, as well as with fine microstructures and no megascopic pores and surface shrinkages. At the cross section of the cup-shaped castings, the grain size, phase compositions and hardness are nearly equally distributed. The NSC processed VW103K alloy show finer average grain size and higher yield strength than that of gravity cast, squeeze cast and rheo-squeeze cast counter parts. Pouring temperature is critical and may influence the microstructure and mechanical properties of NSC processed alloys. With the decrease of pouring temperature from ∼660 to ∼630 °C, the grain size is decreased initially and then coarsened slightly, while the distribution of eutectic phase gets worse continuously. An optimal pouring temperature range of ∼660 to ∼640 °C was obtained for fabricating of VW103K alloy. The mechanisms on formation of fine microstructures in NSC processed VW103K alloys is the combined effects influenced by applied pressure, pouring temperature and the shape of mold cavity.